Hubungan Status Gizi Anak dan Pengetahuan Ibu Tentang Stimulasi Bahasa dengan Perkembangan Bahasa Anak di TK Aisyiyah Bustanul Athfal VI Kota Kediri - Berlian Widya Aurellia; Anindya Hapsari; Rany Ekawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Child development can be assessed from several indicators such as language, and social behavior. Nutritional status and mother's knowledge are supporting factors for children's language development. This study aims to identify the correlation between children's nutritional status and mother's knowledge about language stimulation with children's language development in Aisyiyah Bustanul Athfal VI Kindergarten, Kediri City. Using quantitative method with cross-sectional approach, this research was conducted in July 2023. The sample was selected by purposive sampling. Data collection techniques using questionnaires and Denver II instruments. Data analysis used Spearman's rho test and linear regression tests. We found that there was a significant relationship between mother's knowledge and children's language development (p=0.000) and there was no significant relationship between children's nutritional status and children's language development (p=0.332). The multivariate analysis showed that there was a significant relationship between both independent variables with children's language development (significant value F = 0.000). The conclusion obtained is that there is a simultaneously significant relationship between children's nutritional status and mother's knowledge with children's language development.